2021
DOI: 10.3390/ijms222112079
|View full text |Cite
|
Sign up to set email alerts
|

AMBRA1 Negatively Regulates the Function of ALDH1B1, a Cancer Stem Cell Marker, by Controlling Its Ubiquitination

Abstract: Activating molecule in Beclin-1-regulated autophagy (AMBRA1), a negative regulator of tumorigenesis, is a substrate receptor of the ubiquitin conjugation system. ALDH1B1, an aldehyde dehydrogenase, is a cancer stem cell (CSC) marker that is required for carcinogenesis via upregulation of the β-catenin pathway. Although accumulating evidence suggests a role for ubiquitination in the regulation of CSC markers, the ubiquitination-mediated regulation of ALDH1B1 has not been unraveled. While proteome analysis has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…AMBRA1 is an intrinsically disordered protein that was associated with various tumor progressions, including autophagy, tumorigenesis, proliferation, EMT, and apoptosis ( 26 , 34 , 45 , 48 ). Studies found that AMBRA1 regulates tumorigenesis by targeting the activity of c-MYC, STAT3, and ALDH1B1 ( 23 , 26 , 33 ). In addition, AMBRA1 also regulated tumor proliferation, EMT, migration, and invasion by inhibiting cyclin D, FAK1, and Smad4 ( 34 36 , 38 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMBRA1 is an intrinsically disordered protein that was associated with various tumor progressions, including autophagy, tumorigenesis, proliferation, EMT, and apoptosis ( 26 , 34 , 45 , 48 ). Studies found that AMBRA1 regulates tumorigenesis by targeting the activity of c-MYC, STAT3, and ALDH1B1 ( 23 , 26 , 33 ). In addition, AMBRA1 also regulated tumor proliferation, EMT, migration, and invasion by inhibiting cyclin D, FAK1, and Smad4 ( 34 36 , 38 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMBRA1 is also associated with cancer development, including EMT, migration, invasion, and metastasis ( 26 , 45 , 73 ) ( Figure 4 ). Interestingly, AMBRA1 plays an oncogenic role in hepatocellular carcinoma, metastatic breast cancer, and medulloblastoma, whereas AMBRA1 seems to be a tumor suppressor in colorectal cancer cell, melanoma, and squamous cell carcinoma ( 23 , 24 , 29 , 33 , 38 , 45 , 74 , 75 ). The different effects of AMBRA1 in cancers may be due to diverse types and stages of cancer, as AMBRA1 is an autophagy-associated protein and has different roles depending on the gene context ( 76 ).…”
Section: Role Of Ambra1 In Tumorigenesis and Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is of importance, considering that the CSCs exhibit highly elaborative and effective DNA damage response machinery [ 216 ]. Finally, Baek et al (2021) reported that AMBRA, a negative regulator of several CSC-related genes, negatively regulates ALDH1B1 through K27- and K33-associated ubiquitination [ 203 ].…”
Section: Current Knowledge On the Association Of Aldh1b1 With Cancer ...mentioning
confidence: 99%
“…Overexpression of E3 ligase TRIM25 also promotes oxaliplatin resistance and the stem cell properties in CRC by blocking the K63-linked ubiquitination and degradation of EZH2 mediated by E3 ligase TNF receptor-associated factor 6 (TRAF6) [ 29 ]. TRAF6 also suppresses CSC properties by conjugating K27- and K33-linked ubiquitination to the cancer stemness marker aldehyde dehydrogenase 1 family member B1 (ALDH1B1) and decreasing its enzyme activity [ 30 ]. The autoubiquitination of E3 ligase TRIM21 at K214 and K217 is promoted by the regulator CSN6, thereby decreasing TRIM21-mediated ubiquitination and degradation of Oct1, a transcription activator of another cancer stemness marker ALDH1A1 [ 31 ].…”
Section: The Role Of E3 Ubiquitin Ligases In Crcmentioning
confidence: 99%